Identification of interventions to improve employee morale in physically demanding, repetitive motion work tasks: A pilot case study. Issue 1 (1st January 2021) - Nur, Farjana; Harrison, Dean; Deb, Shuchisnigdha; Burch V, Reuben F.; Strawderman, Lesley
Abstract: Employee morale is a determinant of productivity and retention. This study explores relationships and morale levels between employees and supervisors in a large service industry. An open-ended questionnaire developed based on literature was created to assess morale and motivation, support, incentive, workplace environment, way of motivation, and job satisfaction. This survey was then piloted to managers of hourly product handlers working in a large North American distribution company. Data on existing status of employee morale and the factors influencing morale were collected from managers of three different departments responsible for supervising product handlers. The survey was administered using an online survey tool and answered by a sample of 44 respondents. Poor employee morale and negative attitudes toward their jobs were reported. Influencing factors included minimal pay and hours, lack of motivation, understaffed and unskilled labor, high physical workload, and poor supervision. Manager feedback indicated employees had a lack of understand of company mission and vision but also demonstrated a potential disconnect at the worker and manager levels. Potential interventions such as increasing employee-supervisor interaction, promoting good behavior, offering non-monetary benefits, training, wage rate and employee selection consistency, job redesign, etc. were recommended to management for implementation to improve existing conditions.